Investigation on the impact of human-automation interaction in maritime operations. (1st April 2018) - Pazouki, Kayvan; Forbes, Neil; Norman, Rosemary A.; Woodward, Michael D.
Abstract: The level of automation around the world has grown significantly over the past few decades, and continues to do so. There are many reasons behind this trend, such as safety and potential economic benefits. However, when automation fails or behaves unexpectedly, the impact on the human operator can be severe. In a safety critical operation, such as on the bridge of a ship, the consequences could be catastrophic. The research presented in this paper aims to improve understanding in this important area of study for the maritime industry. An experiment was conducted to assess the awareness of deck officer cadets in the recognition of a developing emergency situation due to failure of the autopilot. Using the results from this experiment and experiences from the aviation industry, the paper provides a potential strategy to improve automation monitoring and accuracy of situation awareness. This has led to the identification of opportunities to improve human-machine interaction. Highlights: The influence of automation on human monitoring performance. Identified automation limitations such as situation awareness in maritime operation. A strategy to improve situation awareness.